Mapping cognitive rehabilitation in diffuse axonal injury (DAI): a case study. - Syed Hassan, Syed Tajuddin; Jamaludin, Husna (Scientific Journals International, 2008)
There has been no report on detailed temporal mapping of traumatic brain injury (TBI), especially diffuse axonal injury (DAI), rehabilitation process. A case study is presented here on four-year tracking of a 24-year old male adolescent with severe DAI. The study aimed to develop a theoretical visual model of TBI (DAI) cognitive rehabilitation, and to validate this model by mapping out the sequence of significant behaviour events. The ensuing spiral cone model concurs with two well-known TBI rehabilitation sequels. The sequence of cognitive rehabilitation should aid in planning interventions in other similar or comparable TBI (DAI) patients.